The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mnfr.201500870
|View full text |Cite
|
Sign up to set email alerts
|

Combined high‐fat‐resveratrol diet and RIP140 knockout mice reveal a novel relationship between elevated bone mitochondrial content and compromised bone microarchitecture, bone mineral mass, and bone strength in the tibia

Abstract: These data show that in the presence of an HF-diet, RSV negatively alters bone health, a process associated with increased mitochondrial content and markers of bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Combined, these data strongly indicate impaired mitochondrial bioenergetics after an HF diet due to impaired ADP sensitivity. Whereas genetic models and interventions that increase mitochondrial content typically have improved insulin sensitivity and glucose tolerance (1,2,6), consumption of the HF diet in the current study, and in others (10,11), paradoxically resulted in increased mitochondrial content despite the induction of glucose intolerance and insulin resistance. Therefore, the notion that mitochondrial dysfunction contributes to the development of insulin resistance has waned in recent years.…”
Section: Discussionmentioning
confidence: 49%
“…Combined, these data strongly indicate impaired mitochondrial bioenergetics after an HF diet due to impaired ADP sensitivity. Whereas genetic models and interventions that increase mitochondrial content typically have improved insulin sensitivity and glucose tolerance (1,2,6), consumption of the HF diet in the current study, and in others (10,11), paradoxically resulted in increased mitochondrial content despite the induction of glucose intolerance and insulin resistance. Therefore, the notion that mitochondrial dysfunction contributes to the development of insulin resistance has waned in recent years.…”
Section: Discussionmentioning
confidence: 49%
“…Many studies have found that high-fat diet (HFD)-induced obesity has a detrimental effect on bone mass and bone microstructure in tibiae, femurs, and vertebrae (Gerbaix et al, 2012;Jatkar et al, 2017;Miotto et al, 2016). A recent study on rats showed that HFD increased the number of osteoclasts and decreased the number of osteoblasts, and the disruption of alveolar bone microarchitecture and horizontal alveolar bone loss was greater in the obese rats than that in the normal rats (Montalvany-Antonucci et al, 2018).…”
mentioning
confidence: 99%
“…A previous report suggested that a correlation between estrogen signaling in mature osteoclasts may act through RIP140; however, this report provided no direct evidence of an estrogen receptor/RIP140 complex, focused on mature osteoclasts, and used a nonphysiologic model of estrogen withdrawal in both reproductive and skeletally immature animals (39). A recent report also showed cancellous changes in a global knockout model of RIP140; however, given RIP140's known systemic effects, a direct correlation to osteoclast activity is unclear (40). Given RIP140's wide-spectrum activities, such as in metabolism and inflammation, nondiscriminatingly targeting RIP140 might negate the beneficial impact of RIP140 ablation in osteoclast macrophage precursors (15)(16)(17).…”
Section: Discussionmentioning
confidence: 86%